Device for studying uneven rotation of crankshaft - A. E. Korneev (Омский научный вестник)
The main topic of the article is the choice of the direction and implementation of the use of electronic measuring instruments and monitoring of the working process occurring in the diesel internal combustion engine. For this purpose, an analysis is performed and a device is created that allows controlling the uneven rotation of the engine crankshaft containing photoelectron sensors, one of which allows reading the moment of passing the upper dead point, the other is designed to control the angular speed of the flywheel. The device converts the signals of these sensors into the form necessary for visualization of the working periodic process on the oscilloscope screen. The article presents a block diagram of the device and its amplitude-frequency characteristic. This device can be used for research and development work to improve fuel supply systems in internal combustion engines.